A Cognitive ’Just’ Brand Model:How Sustainable Is It? - Anand, Sandip (Indian Journal of Marketing, 2009)
This study is based upon the analysis of framework represented through a model of cognitive justice. It analyses the model in the context of ICT, e-microfinance and try to draw the argument upon its sustainability. The study is an attempt to analyse the concepts of consumer justice, its relationship with the marketing and finally how relevant these concepts are in the changing environment of technology. Here the methodology used is analysis of available literature and scenario building analysis. The analysis indicates how ICT (Information and Communication Technology) could utilize e-microfinance to enable farmers in all possible ways to produce and deliver goods through community participation. Scenario analysis reflect upon corporate and community relationship and analyze viable business options. It is inferred from analysis that e-microfinance leads to cognitive justice for farmers and business sustainability for corporations as well.